Finansowanie Kościołów i związków wyznaniowych ze środków publicznych: Analiza debat politycznych nad likwidacją Komisji Majątkowej i Funduszu Kościelnego (Politeja, 2017)
Public funding of churches and religious associations in Poland: Analysis of political debates on the liquidation of the Church Property Commission and the Church FundThe paper contains a case study of the political debate concerning public funding for the religious institutions. It deals with the parliamentary discussions in the years 2004‑2015 on the abolishing of two public bodies: Church Property Commission (Komisja Majątkowa) and Church Fund (Fundusz Kościelny). The paper has two main objectives. First of them is providing the description of the debate (most important themes in the discourse, argumentative strategies, rhetorical instruments used by the interlocutors). The characteristics of the discourse let us draw a picture of the social relations and the place of religion in the public sphere. Therefore, the second objective of the paper is to describe the dominant narratives in the public debate on the role of religion in society and the state.